Menarik Perhatian Konsumen : Peran Media Sosial dan Citra Merek dalam Pembelian Smartphone Samsung - Harefa, Trisman; Riki, Riki (Bahtera Inovasi, 2025)
A smartphone is a cellular phone with a built-in microprocessor, memory, display and modem. With the development of the smartphone industry, manufacturers are creating gadgets that are increasingly sophisticated, top-notch and designed for their consumers. Therefore, those who are rebuilding their business must compete hard to improve their marketing strategies and sales of smartphone products. Therefore, this justifies the conductivity of research on consumer purchasing behavior towards this smartphone. This study was conducted to determine and analyze the effect of the role of social media and Brand Image on Samsung Smartphone Purchasing Decisions in Batam City. The research design uses descriptive quantitative methods and data analysis using Smart Partial Least Square analysis tools with a sample of 140 respondents. Research results: The R-square value is 0.375. This value says that the role of social media and brand image simultaneously influence purchasing decisions is 37.5%. The rest are other variables apart from the pattern variables in this study.